RETROSPECTIVE RADIATION SITUATION OF THE URDZHAR DISTRICT OF THE ABAI REGION (Eurasian Journal of Ecology, 2024)
Atmospheric tests, which became the main cause of radioactive pollution of the environment, at the Semipalatinsk nuclear test site were completed in 1962. The People's Republic of China (PRC) conducted nuclear tests in the atmosphere from 1965 to 1980. The settlements of the Urdzhar district of the Abai region are located at a distance of 600-700 km from the Semipalatinsk test site and at a distance of 900-1100 km from the chinese Lob-Nor test site. The main scientific issue of the entire study is to assess the contribution of ionizing radiation at low dose range due to the Lob-Nor nuclear tests to the formation of the radiation situation in the southern part of the Abai region. An important aspect of the research will be to study the impact of nuclear tests at the Lob-Nor test site (PRC) on the population of Kazakhstan. The paper presents the analysis results of previously unpublished archival data on the parameters of radiation-hygienic situation in the study area. According to the content of radioisotopes, caesium-137 and strontium-90, in soil of Urdzhar district, two peaks are distinguished, which occurred in June 1967 and July 1973 and significantly exceed the indicators of 1963 and the national average levels of soil contimination.